The ethnographic research process: ethical considerations - Restrepo, Eduardo (Instituto de Altos Estudios Sociales, 2016)
Building on two ideal-types that represent the antithesis of the expected ethi - cal position of a researcher (the thief ethnographer and the indifferent ethnographer), I explore the limits and challenges of finding an ethical position in contemporary ethnographic practice. In contrast with these two figures -the thief ethnographer and the indifferent ethnographer- my position is that in any type of ethnographic research--not exclusively those in which there is an overt identification with subaltern struggles--ethical considerations require the figure of the committed ethnographer.